Visual Resistance: How Indonesian Artists Depict the Palestinian Struggle (Palestine Issues on Indonesian Society, 2025)
This paper explores the role of Indonesian artists in visually representing the Palestinian struggle for freedom and justice. Through an analysis of contemporary visual art, including paintings, murals, and digital media, the study examines how Indonesian artists use their craft as a form of political resistance, solidarity, and advocacy for Palestinian rights. Drawing on examples from prominent Indonesian artists and grassroots art movements, the paper identifies recurring themes in the depiction of Palestinian suffering, resistance, and hope. The study also explores the intersection of artistic expression and political activism, considering how visual art is used to raise awareness, mobilize public sentiment, and advocate for change within Indonesian society. It argues that Palestinian issues in Indonesian art are not merely a form of international solidarity but also a way of communicating broader messages of justice, anti-imperialism, and Muslim solidarity. The paper further examines how this visual resistance intersects with other forms of activism, such as social media campaigns and public protests, as well as the implications for the role of art in shaping public opinion and policy discourse.